Acceptance of generic drugs by users from sector C, D and E sectors in three zones of Lima - Canales M, Loly F. (2012)
The aim of this research was to determine the acceptability of generic drugs (GD) among users that belong to the sectors C, D and E in Metropolitan Lima, as well as the grade of knowledge, confidence and possible barriers in its consumption. A survey was conducted in zones where over than the 85% of the population belongs to this sectors .The tool consisted in a questionnaire of 11 open and closed questions. It was identified four dimensions that influenced on the acceptance of the generic drugs: information, security/efficacy, consumption and access. The analysis of the results obtained by the scale of Stanones set the media average of 3,2 among the four dimensions whichs means a REGULAR dimension. It was found a high consumption of GD with a media of 4,9; this accessibility is linked to the low cost instead than confidence in the GD, since there are doubts about its efficiency.